Analysis of the Application of Mangrove Rehabilitation Structures on Mangrove Growth and Calculation of Carbon Stocks in the Coastal Area of Demak, Indonesia - Elinna Putri Handayani; Mochamad Arief Budihardjo; Denny Nugroho Sugianto (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Mangroves participate in controlling climate change by acting as the lungs of the world through the absorption and storage of blue carbon. The high-standing water on the land that must be rehabilitated is one of the obstacles encountered, so a special strategy is needed, namely, implementing a mangrove rehabilitation media structure using the demplot mangrove method. This study aimed to analyze mangrove growth based on the application of mangrove rehabilitation media structures and to calculate potential carbon stocks based on the value of tree biomass from mangrove rehabilitation monitoring. In this study, tree height and diameter were measured and linked to the water quality and frequency of inundation. Mangrove carbon reserves were also calculated based on biomass values. Good growth in the height and diameter of mangroves occurred in Avicennia lanata stands with an inundation frequency of 6 h/day. The largest projection of potential carbon stocks from the results of monitoring mangrove rehabilitation was also stored in Avicennia lanata mangrove stands at 0.3467 kg/tree (60 months), 0.6287 kg/tree (120 months), and 0.9107 kg/tree (180 months).